Genetic Divergence Analysis in Perilla [Perilla frutescens (L.) Britton] - HUSSAIN, SAFIQUL; CHANGKIJA, S.; HORE, D. K. (Indian Journal of Hill Farming, 2015)
Divergence analysis using Mahalanobi’s D2 statistic was carried out in Fifty Perilla (Perilla frutescens (L.) Britton) accessions, collected from different parts of northeastern region of India including one exotic collection from Australia. All the fifty genotypes were grouped into nine clusters depending on their genetic distances. Interestingly, the cluster-I comprised of forty two genotypes, while the remaining eight genotypes were distributed over eight different clusters. The clustering pattern of the genotypes indicates that genetic diversity does not necessarily relate to geographical diversity. Inter cluster distances varied from 11.16 between cluster-IV and cluster-V to 34.02 between cluster-III and cluster- VIII. The contribution of individual traits to the divergence reveals that 1000-seed weight contributed maximum (31.18%) towards genetic divergence followed by days to maturity (19.84%) and number of leaves per plant (18.69%).